Impact of brand strength and customer reviews: the case of rural tourism inns in China / Siyu Peng, Nicholas Su Miew Sing - Peng, Siyu; Su Miew Sing, Nicholas (Universiti Teknologi MARA Cawangan Sarawak, 2020)
As e-commerce continues to become an integral part of our lives, more and more purchase decisions are being made online. A significant contribution leading to such purchases stem from a few key factors, one of which, is customer reviews. Reviews are based on consumer experience and are increasingly necessary on e-commerce sites and platforms. Another key factor is the role brands play in influencing purchase decisions. A brand is an intangible asset of a company where brand value reflects the degree of differentiation a brand has over competitors. Most consumers judge the quality of an online product based on reviews and brands. This paper explores the question of how online product reviews and brands affect product sales on travel websites, using Ctrip.com as a case study. The study uses the user recommendation rate, the total score, the total number of reviews and brand strength to draw a relationship that suggests online reviews and brand strength impact product sales. The results demonstrate that there is a positive impact on product sales for high review scores on weak-branded inns; and the sales volume of strong branded inns are more prominently affected by the number of comments and user recommendation rate.